Prevalencia de violencia de género personas en situación de discapacidad en el cantón Calvas - Vivanco Escudero, Arianna Maoli (2023)
Gender-based violence plays a fundamental role in Ecuador; according to various studies, individuals with disabilities are three times more vulnerable to experiencing some form of violence, and women are 10 times more likely to be victims of sexual violence. The objective was set to determine the prevalence of gender-based violence in people with disabilities in the Calvas canton. From January to March 2022, a quantitative, observational, cross-sectional project was carried out, employing a randomly selected sample of 112 individuals from a population of 1046 people with disabilities. Using this method, it was possible to ascertain the existence of genderbased violence in people with disabilities, with a reported violence rate of 24.10%. Among these cases, 66.67% were female, 44.44% had intellectual disabilities, and 77.07% of the victims reported experiencing psychological violence. In conclusion, the research confirmed the hypothesis as true, revealing the presence of gender-based violence in people with disabilities in the Calvas canton, predominantly affecting women and individuals with intellectual disabilities. However, due to a lack of information, there is a need to emphasize the development of new research, dissemination, and promotion of activities for the detection, control, eradication, and prevention of violence